Guyana : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guyana. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation highlights that Guyana's economic growth strengthened in 2018 with broad-based expansion across all major sectors. The medium-term prospects are very favorable as oil production is on schedule to begin in early 2020. Economic growth is projected at 4.4 percent in 2019, extending the broad-based expansion across all major sectors. Policies to fortify the fiscal policy framework to ensure effective use of the new-found oil wealth; develop the necessary infrastructure for a suitable monetary policy framework that facilitates adjustment to oil price shocks while maintaining price stability; and reforms to enhance competitiveness, promote economic diversification, strengthen governance, and achieve inclusiveness. The passage of the Natural Resource Fund legislation is a critical step toward effective management of Guyana's natural resource wealth. In order to ensure that fiscal discipline is maintained and spending ramps up at a pace in line with absorptive capacity, the fiscal framework should be enhanced to prevent deficits.